2017
DOI: 10.3389/fphys.2017.01026
|View full text |Cite
|
Sign up to set email alerts
|

Murine Precision-Cut Kidney Slices as an ex vivo Model to Evaluate the Role of Transforming Growth Factor-β1 Signaling in the Onset of Renal Fibrosis

Abstract: Renal fibrosis is characterized by progressive accumulation of extracellular matrix (ECM) proteins, resulting in loss of organ function and eventually requiring renal replacement therapy. Unfortunately, no efficacious treatment options are available to halt renal fibrosis and translational models to test pharmacological agents are not always representative. Here, we evaluated murine precision-cut kidney slices (mPCKS) as a promising ex vivo model of renal fibrosis in which pathophysiology as well as therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Figure 2a provides a quick comparison of the magnitude of the culture-induced transcriptional changes across PCKS without detailing marker genes, while Figure 2b-d and Figure S2 provide detailed expression data. In line with previous reports [22,42], preparation and culturing of the slices triggered the early onset of fibrosis and inflammation and activated both the TGFβ and PDGF pathways in PCKS prepared from healthy murine and human kidneys. In particular, 13 out of 14 tested genes were upregulated at 48 h in mPCKS, while hPCKS showed culture-induced upregulation of eight genes, namely COL1A1, SERPINH1, PLOD2, TGFB, SERPINE1, PDGFRB, TNF, and IL-6 ( Figure 2 and Figure S2).…”
Section: Culture-driven Inflammatory and Fibrogenic State Of Pckssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 2a provides a quick comparison of the magnitude of the culture-induced transcriptional changes across PCKS without detailing marker genes, while Figure 2b-d and Figure S2 provide detailed expression data. In line with previous reports [22,42], preparation and culturing of the slices triggered the early onset of fibrosis and inflammation and activated both the TGFβ and PDGF pathways in PCKS prepared from healthy murine and human kidneys. In particular, 13 out of 14 tested genes were upregulated at 48 h in mPCKS, while hPCKS showed culture-induced upregulation of eight genes, namely COL1A1, SERPINH1, PLOD2, TGFB, SERPINE1, PDGFRB, TNF, and IL-6 ( Figure 2 and Figure S2).…”
Section: Culture-driven Inflammatory and Fibrogenic State Of Pckssupporting
confidence: 90%
“…We showed that injury inflicted by slice preparation and sustained by culturing for 48 h affects the transcriptional program of PCKS, dictating faster changes in gene regulation in murine PCKS compared to human PCKS. Independent of the species, PCKS responded to culturing by an increased expression of ECM-and inflammation-related gene markers accompanied by the activation of TGFβ and/or PDGF signaling pathways, in line with previous reports [22,42]. Species differences in injurious responses included unchanged mRNA levels of fibronectin, TGFβ receptor 1, PDGFB ligand and interleukin (IL)-1B in human PCKS as opposed to their increased transcription in mouse PCKS, which might suggest a delayed response of human PCKS, and, therefore, a longer incubation time (beyond 48 h) might be needed to induce changes in these transcripts.…”
Section: Pcks Injurious Responses To the Culturingsupporting
confidence: 90%
“…Normal mouse precision cut kidney slices (PCKS) cultured in 80% oxygen have increased inflammatory gene expression within 3 hours, whilst fibrosis gene expression was elevated by 96 hours. Treatment with LY2109761, a TGFβ receptor inhibitor, blunted the fibrogenic response confirming that spontaneous fibrosis was in part TGFβ-dependant [31]. Using this system, successful myofibroblast-specific targeting of an anti-fibrotic IFNγ-peptide conjugate (PPB-PEG-IFNγ) limited TGFβ-induced fibrogenic gene expression and collagen deposition [32], providing evidence that peptide therapies can penetrate tissue slices and exert biological effects.…”
Section: Precision Cut Slicesmentioning
confidence: 99%
“…With this in mind, in this study we aimed at comparing nanoparticle impact in lungs, liver, and kidneys, selected as three of the major organs for nanosafety assessment (Olinga and Schuppan 2013;Sauer et al 2014;Stribos et al 2017).…”
Section: Introductionmentioning
confidence: 99%